2015
DOI: 10.1080/10494820.2015.1041405
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods approach to the assessor's targeting behavior during online peer assessment: effects of anonymity and underlying reasons

Abstract: This study examined the effects of identity revelation and concealment on the number of times students' work was assessed in an online peer assessment context. It also examined the underlying reasons guiding the assessor's targeting behavior. Two fifthgrade classes participated. The one-group pretest-posttest experimental research design coupled with qualitative research method was adopted. The results from social network analysis (SNA) showed a high redundancy rate for both high-and lowtargeted assessees in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
(56 reference statements)
2
11
0
Order By: Relevance
“…Considering the intervals, the difference between the teacher and peer raters was statistically significant in the online and face-to-face assessment environments, but it was insignificant in anonymous assessment. The qualitative data were performed to examine why teachers and peers had similar scoring in anonymous assessment and anonymity was found to be an important factor for this situation, confirming the previous research (Cheng & Tsai, 2012;Chester & Gwynne;Pope, 2005;Yu & Sung, 2016;Vickerman, 2009). Thus, anonymity provides a safe environment for peer raters, which results in fairer assessment as there is no over-scoring (Freeman & McKenzie, 2000;Panadero et al, 2013).…”
Section: Conclusion and Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Considering the intervals, the difference between the teacher and peer raters was statistically significant in the online and face-to-face assessment environments, but it was insignificant in anonymous assessment. The qualitative data were performed to examine why teachers and peers had similar scoring in anonymous assessment and anonymity was found to be an important factor for this situation, confirming the previous research (Cheng & Tsai, 2012;Chester & Gwynne;Pope, 2005;Yu & Sung, 2016;Vickerman, 2009). Thus, anonymity provides a safe environment for peer raters, which results in fairer assessment as there is no over-scoring (Freeman & McKenzie, 2000;Panadero et al, 2013).…”
Section: Conclusion and Discussionsupporting
confidence: 67%
“…A conceptual basis regarding the possible effect of anonymity indicates that students' feedback will differ depending on whether their identities as assessors are revealed (Yu & Sung, 2016). Publicly assessing their peers may cause students to feel uncomfortable and experience stress (Pope, 2005).…”
Section: Anonymity In Peer Assessmentmentioning
confidence: 99%
“…The theoretical foundations with regard to the possible impact of anonymity imply that students will enact different feedback behavior depending on whether their identity as assessors is revealed (Yu and Sung 2015). It is this approach that the current study adopts, and Yu and Sung (2015) provide two perspectives from social psychology that help to support and contextualize this adoption.…”
Section: Anonymity As An Instructional Scaffold Within Peer Assessmentmentioning
confidence: 98%
“…Peer assessment (PA) is a peer-assisted, collaborative learning arrangement that includes students assessing their fellow students' performance by providing feedback, which could be quantitative in nature (i.e., grades or ratings across assessment criteria) and/or qualitative (written or oral comments) (Topping 1998). The process of assessing and commenting on the strengths and weaknesses of peers' work can help familiarize the assessor with the evaluation criteria and, in this way, help to develop knowledge on what constitutes good work and what needs to be avoided (Yu and Sung 2015). Numerous studies on PA have shown various benefits for the learning process, such as improved student motivation and improved conceptual understanding, communication skills, and self-assessment skills (e.g., Falchikov and Goldfinch 2000;Topping 2009).…”
Section: Introductionmentioning
confidence: 99%